Control of F plasmid replication by a host gene: evidence for interaction of the mafA gene product of Escherichia coli with the mini-F incC region. - Wada, C (1984)
Replication of F (including mini-F) and some related plasmids is known to be specifically inhibited in mafA mutants of Escherichia coli K-12. We have now isolated and characterized mini-F mutants that can overcome the replication inhibition. Such plasmids, designated pom (permissive on maf), were obtained spontaneously or after mutagenesis with hydroxylamine or by transposon (Tn3) insertion. In addition to their ability to replicate in mafA mutant bacteria, the pom mutant plasmids exhibit an increased copy number and resistance to "curing" by acridine dye in the mafA+ host. In agreement with these results, Tn3-induced pom mutants were found to carry Tn3 inserted at the incC region of mini-F DNA, known to be involved in incompatibility, control of copy number, and sensitivity to acridine dye. Furthermore, three of the seven mini-F plasmids tested that carry Tn3 within the tandem repeat sequences of the incC region (previously isolated by other workers) exhibit all the phenotypes of pom plasmids, the ability to replicate in the mafA strain, and high copy number and acridine resistance in the mafA+ strain. The rest of the plasmids that contain Tn3 just outside the tandem repeats remain wild type in all these properties. These results strongly suggest that the putative mafA gene product of host bacteria controls mini-F replication through interaction with the incC region.